Analysis of Chinese Commercial Banks' Risk Management Efficiency Based on the PCA-DEA Approach. (27th October 2021) - Shi, Xiao; Yu, Wenqi
Abstract : As a special type of enterprises with high risks, Chinese commercial banks' risk management plays an important role in banks' business process. Measuring and improving the risk management efficiency of the Chinese commercial banking system has recently attracted increasing interest. Previous studies analyze the business performance of commercial banks from the perspective of the overall management level of banks, and few articles focus on the risk management ability of banks. This paper evaluates the technical efficiencies of Chinese commercial banks' risk management by the DEA-BCC model with window analysis to come up with some recommendations for policy makers. The technical efficiency is then decomposed into pure technology efficiency and scale efficiency. According to the banking risk supervision indicators released by the China Banking Regulatory Commission, we choose the indicators of 26 commercial banks' risk management during the period of 2011 to 2019. Principal component analysis (PCA) is applied to delete redundant input indicators. The paper gives a dynamic evaluation of technology efficiency, pure technology efficiency, and scale efficiency. The main empirical results are as follows: (1) the technical efficiency of Chinese commercial banks' risk management is low, and the differences among three different types of banks are large. (2) The pure technology inefficiency of Chinese commercial banks' risk management has become a key factor restricting the improvement of the risk management of the Chinese banking industry. (3) The Chinese commercial banks' risk management faces a serious problem which is economies of scale. (4) The technical efficiencies of Chinese commercial banks' risk management fluctuate greatly, and management capabilities need to be enhanced urgently.